Phenomenological ethics of Edmund Husserl as ethics of “Rrenovation” and personal ethics - Vargas Bejarano, Julio César (Estudios de Filosofía, 2007)
The relatively recent publication of the press articles in the Japanese magazine Kaizo, entitled “Renovation of man and culture” (1923-1924) and the ethical classes given by Husserl in the years 1920 and 1924 enable us to approach to the new course that his ethical reflections took. Likewise, these texts allow us to understand the critical position of Husserl to his rst version of his Ethics, which was characterized by being a universal doctrine of values based on a formal Axiology. Since the twenties Husserl presents a novel conception of his Ethics, and its main foundation is the resolution of the radical subject and volitive by means of a life devoted to responsibility and love. This work shows how such a change was possible and the general traits of this version of Ethics that can also be termed “personalistic”.